1999
DOI: 10.1007/s11745-999-336-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the sterol composition of dominant antarctic zooplankton

Abstract: The composition of free sterols was determined in Antarctic zooplankton species with various feeding behaviors. In the Southern Ocean, the dominant calanoid copepods Calanoides acutus, Calanus propinquus, Metridia gerlachei, and Euchaeta antarctica were investigated during different seasons and compared with the euphausiids Euphausia superba, E. crystallorophias, and Thysanoessa macrura. In addition, the Arctic copepods Calanus hyperboreus, C. glacialis, and C. finmarchicus were studied for comparison. Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…C 27 Diunsaturated sterols, particularly cholesta-5,22-dienol, were found in high relative abundance in zooplankton from fish and fishless enclosures. Cholesta-5,22-dienol has already been reported as an important constituent of the sterol fraction of zooplankton (Prahl et al 1984(Prahl et al , 1985Harvey et al 1987;Mühlebach et al 1999). This sterol was not observed in seston from both fish and fishless enclosures.…”
Section: Zooplanktonmentioning
confidence: 98%
See 2 more Smart Citations
“…C 27 Diunsaturated sterols, particularly cholesta-5,22-dienol, were found in high relative abundance in zooplankton from fish and fishless enclosures. Cholesta-5,22-dienol has already been reported as an important constituent of the sterol fraction of zooplankton (Prahl et al 1984(Prahl et al , 1985Harvey et al 1987;Mühlebach et al 1999). This sterol was not observed in seston from both fish and fishless enclosures.…”
Section: Zooplanktonmentioning
confidence: 98%
“…Surprisingly, cholesta-5,24-dienol was either present in low proportion (in fishless enclosures) or absent (in fish enclosures), while it has been reported as the second most important sterol in many crustaceans (Prahl et al 1984(Prahl et al , 1985Harvey et al 1987;Mühlebach et al 1999). It is well established that crustaceans have no capacity for de novo sterol biosynthesis (Goad 1981).…”
Section: Zooplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterol profiles are not well studied in copepods, but one major difference did occur between profiles from our study and previous work. Desmosterol (cholesta-5, 24-dien-3β-ol) was notably absent in the copepods in the present study, a compound which was often the second most abundant sterol found in zooplankton (Harvey et al 1987, Serrazanetti et al 1992, Mühlebach et al 1999. Desmosterol is usually thought to occur because it is an intermediate in the conversion of dietary phytosterols to cholesterol (Goad 1978).…”
Section: Discussionmentioning
confidence: 52%
“…Most species within a class (Crustacea) or even within a phylum (Arthropoda) are considered to display similar biochemical capabilities for sterol metabolism (Goad 1981;Rees 1989). Mühlebach et al (1999) examined the sterol content in the guts of Antarctic copepods and euphausiids and found that the cholesterol content in the guts of the calanoid copepods was 22.1-60.5% and that of euphausiids was more than 75% of the total sterols, although no indication of the dietary phytoplankton was given. Thus, if sterols in the gut are incorporated in SCEs, cholesterol should form a significant portion of sterols in SCEs, although the contribution of sterol esters was estimated to be less than 1% of total sterols in the guts of copepods (Mühlebach et al 1999).…”
Section: Introductionmentioning
confidence: 99%